2022
DOI: 10.3389/fimmu.2022.932228
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Microbiotas in Hematopoietic Stem Cell and Organ Transplantation

Abstract: The human microbiota heavily influences most vital aspects of human physiology including organ transplantation outcomes and transplant rejection risk. A variety of organ transplantation scenarios such as lung and heart transplantation as well as hematopoietic stem cell transplantation is heavily influenced by the human microbiotas. The human microbiota refers to a rich, diverse, and complex ecosystem of bacteria, fungi, archaea, helminths, protozoans, parasites, and viruses. Research accumulating over the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 255 publications
0
6
0
Order By: Relevance
“…Since the immune system regulates microbiota composition ( 16 ) and chemotherapy ( 17 ), radiotherapy ( 18 ), and antibiotics ( 19 ) have detrimental effects on the microbiota, drastic alterations in the gut microbiota have been reported in allo-HSCT recipients, including loss of bacterial diversity and blooms of potentially pathogenic species ( 20 ). Recent evidence shows these alterations extend to other microbiota ( 21 ), including the relatively more stable oral microbiota ( 22 26 ). More importantly, the pre-transplant microbiota and the extent of microbiota damage during allo-HSCT are associated with allo-HSCT complications and outcomes, so that gut and oral microbiota provide biomarkers in the allo-HSCT setting ( 24 , 25 , 27 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the immune system regulates microbiota composition ( 16 ) and chemotherapy ( 17 ), radiotherapy ( 18 ), and antibiotics ( 19 ) have detrimental effects on the microbiota, drastic alterations in the gut microbiota have been reported in allo-HSCT recipients, including loss of bacterial diversity and blooms of potentially pathogenic species ( 20 ). Recent evidence shows these alterations extend to other microbiota ( 21 ), including the relatively more stable oral microbiota ( 22 26 ). More importantly, the pre-transplant microbiota and the extent of microbiota damage during allo-HSCT are associated with allo-HSCT complications and outcomes, so that gut and oral microbiota provide biomarkers in the allo-HSCT setting ( 24 , 25 , 27 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of microbiome studies were performed using ribosomal DNA (rDNA) based sequencing methods designed for bacterial and fungal 16/23S, 18/28S or ITS region rDNA sequences, respectively, thus neglecting the archaeome, non-fungal eukaryome, and the DNA virome (Borrel et al 2020, Kurilshikov et al 2021, Richard and Sokol 2019, Sen and Thummer 2022, Stockdale and Hill 2021, Vandeputte et al 2017, Yalcin et al 2022, Zhernakova et al 2016). rDNA sequencing is a well-established, scalable, and cost-effective technology; it has, however, important limitations as it bears potential amplification-induced biases in bacteriome/mycobiome composition estimates and challenges in reliably assigning accurate species - or genus-level labels (Edgar 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the impact of T-cell depletion during bone marrow transplantation on the microbiota is an area that requires further research. The gut microbiota has been shown to modulate the human immune system, and its impact on HCT outcomes and transplant rejection risk has been increasingly recognized 11,12 . Research in human cohorts has revealed that the composition of the gut microbiota prior to transplantation can influence the likelihood of GVHD development and the overall success of the transplant.…”
Section: Introductionmentioning
confidence: 99%